Addressing the Need for Progress in Special Education: Understanding Endrew F. and the Role of Special Educators - Kern, Laura; George, Heather Peshak; Evanovich, Lauren L.; Martinez, Stephanie (Journal of the American Academy of Special Education Professionals, 2019)
The Supreme Court case of "Endrew F. v. Douglas County District RE"-1 (2017) has renewed interest in the Free and Appropriate Public Education (FAPE) mandate of the Individuals with Disabilities Act (IDEA). The court’s ruling expands the term "appropriate" to a consideration of progress for academics and behavior. This shift has significance to many who work with students with disabilities in schools. Specifically, special educators will need to ensure that they are assessing and monitoring academics and behavioral, such as incorporating functional behavior assessments (FBAs) into the development of appropriate behavior intervention plans (BIPs) and considering overall progress during Individualized Education Programs (IEP) development. This paper will address the history of IDEA, its connection with FAPE, and discuss the seminal cases of "Rowley" and "Endrew F. and their implications for IEP teams. Considerations and recommendations for addressing FAPE for students will be provided, focusing on implications for the IEP, Multi-tiered Systems of Support (MTSS), and Behavior Intervention Plans (BIPs).